1998
DOI: 10.1093/ps/77.7.964
|View full text |Cite
|
Sign up to set email alerts
|

Lymphokine-augmented activation of avian heterophils

Abstract: Heterophils are important mediators of innate resistance in poultry, especially in young birds that have not yet developed an acquired immune response. Invasion of the intestinal mucosa by Salmonella spp. initiates the recruitment of large numbers of heterophils to the lamina propria. Thus, the heterophilic response can control, but not eliminate, bacterial numbers in the bird until development of acquired immunity. Unfortunately, chicks and turkey poults are highly susceptible to Salmonella infections during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Their functions include chemotaxis, adherence, phagocytosis and killing bacteria, with the activity level being age-dependent in many birds (Kogut et al 1998).…”
Section: Basic Functional Dependencies Of Cells Involved In the Localmentioning
confidence: 99%
“…Their functions include chemotaxis, adherence, phagocytosis and killing bacteria, with the activity level being age-dependent in many birds (Kogut et al 1998).…”
Section: Basic Functional Dependencies Of Cells Involved In the Localmentioning
confidence: 99%
“…It has been reported that Lid reduces the MFI of CD11b by half in human leukocytes [13]. Lan et al [14] reported that exposure of Lid-treated cells to hypoxia-reoxygenation resulted in lower neutrophil CD18 expression compared with controls. These results indicate that reduction of CD18 expression by Lid reduces firm adhesion of granulocytes to the endothelium and thus reduces granulocyte extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…L-selectin, which is also referred to as CD62L, is a surface molecule constitutively expressed and functional in all granulocytes. CD62L is involved in initial contact of the granulocytes with the endothelium and mediates leukocyte rolling in order to find the sites of infections [14]. Beta2 integrins, also referred to as CD11/CD18 adhesion molecules, mediate firm adhesion of granulocytes to the endothelium following the rolling process by L-selectin, and they then facilitate granulocyte extravasation [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sob estímulo, expressam receptores de membrana responsáveis pela aderência e migração pelo endotélio vascular, dirigindo-se por quimiotaxia ao sítio de infecção. Após fagocitose, há a morte do agente infeccioso por meio de enzimas líticas e agentes oxidantes (RODRÍGUEZ et al, 1997;KOGUT et al, 1998;FARNELL et al, 2003).…”
Section: Introductionunclassified